INSTITUTIONAL SUPPORT OF ETHNOPOLITICS OF CENTRAL AND EASTERN EUROPE (on Example of Bulgaria, Romania and the Slovak Republic): EXPERIENCE FOR UKRAINE - Popok E.A. (Pressing Problems of Public Administration, 2016)
The article examines the institutional support of ethnopolitics of Central and Eastern Europe Countries,post-socialist Bulgaria, Romania and the Slovak Republic, neighboring to Ukraine.